PENGARUH MODAL INTELEKTUAL DAN MODAL KERJA TERHADAP NILAI PERUSAHAAN DENGAN KINERJA PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Tarigan, veranita Br; Hadiprajitno, Paulus Theodorus Basuki (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
This study analyzes the impact of Intellectual Capital and Working Capital on company value mediated by company performance of manufactures companies listed in the Indonesia Stock Exchange in 2017 – 2020. The data used in this study are secondary data. The method in selecting the sample is purposive sampling. The number of samples in this study were 94 companies. The research data analysis technique used path analysis. The results show that intellectual capital has a positive effect on company performance but has no effect on company value. Working capital has a positive effect on company performance but has no effect on company value. Company performance is not able to be an intervening in the relationship between intellectual capital and working capital to firm value